Environmental barrier coating bonding layer material, preparation method thereof and environmental barrier composite material
By using Si, HfO2 and Y2O3 in the environmental barrier coating bonding layer material, the molar ratio and content are adjusted to form the main phase coating of HfSiO4, the problem of failure of the existing coating at high temperature is solved, and good performance in the range of 1350°C to 1500°C is achieved.
Patent Information
- Application Number
- CN202411777797.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-28
AI Technical Summary
The existing environmental barrier coating bonding layer materials have failure problems caused by oxygen permeation and phase transition at high temperatures, making it difficult to meet the service temperature requirements of above 1500°C.
Si, HfO2 and Y2O3 are used as coating systems, and the main phase coating of HfSiO4 with high temperature stability and toughness is formed by adjusting the molar ratio of HfO2 and Si and the content of Y2O3.
The coating has a long service life at 1350°C and still has good protective performance and temperature bearing capacity at 1500°C. It is suitable for different service environments.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental barrier coatings, and in particular to an environmental barrier coating bonding layer material, a preparation method thereof and an environmental barrier composite material. Background Art
[0002] Environmental barrier coating (EBC) is an indispensable protective coating on the surface of high-temperature components of ceramic matrix composites (CMC) of high-performance aircraft engines, which can effectively prevent CMC components from being corroded by water vapor-oxygen coupling. Traditional environmental barrier coatings use Si layer as the bottom bonding layer, but Si is easily oxidized to SiO 2 , SiO 2 It is very easy to be penetrated by oxygen and oxygen ions, causing the bonding layer to fall off and fail, and SiO 2 Phase change will occur at a certain temperature, and the resulting volume expansion will increase the stress at the interface between the substrate and the coating. 2 (melting point is 2850℃) Modification of the Si bonding layer can reduce the penetration of oxygen into the Si bonding layer. It is the first choice for the bonding layer material system of the current new generation of EBC. This system has been proven to be able to be used stably for a long time below 1350℃.
[0003] As the turbine inlet temperature of aircraft engines continues to rise, it is urgent to develop coating systems that can be used at temperatures of 1500°C or even higher. 2 HfO in the system 2 The content of HfO can effectively improve the temperature bearing capacity of the coating. 2 The transition from c phase to m phase occurs at 1500℃, which limits the application of this system at higher service temperatures. 2 Modifying the coating to meet the requirements of use at different temperatures is the future development direction of environmental barrier coating bonding layer materials. Summary of the invention
[0004] The technical problem solved by the present invention is to provide an environmental barrier coating bonding layer material. The bonding layer material provided in the present application can make the coating have a long life at 1350°C and improve the temperature bearing capacity at 1500°C.
[0005] In view of this, the present application provides an environmental barrier coating bonding layer material, including Si, HfO 2 and Y 2 O 3 , the HfO 2 and the Y 2 O 3 The molar ratio of HfO is x:(1-x). 2The molar ratio of x to Si is (0.2:0.8) to (0.8:0.2); wherein 0.8≤x≤0.9.
[0006] Preferably, the HfO 2 The molar ratio of Si to the Si is (0.4:0.6) to (0.6:0.4).
[0007] The present application also provides a method for preparing the environmental barrier coating bonding layer material, comprising the following steps:
[0008] S1) HfOCl 2 8H 2 O and Y 2 O 3 Mixing in a solution in a molar ratio of x:(1-x) to obtain a mixed solution, wherein 0.8≤x≤0.9;
[0009] S2) The mixed solution is sequentially precipitated, filtered, washed, calcined, and sintered to obtain HfO 2 and Y 2 O 3 Mixed powder;
[0010] S3) mixing the mixed powder and Si, ball milling, and then mixing with a binder to obtain a mixed slurry; HfO in the mixed powder 2 The molar ratio of Si is (0.2:0.8)~(0.8:0.2);
[0011] S4) spray-drying the mixed slurry and then sintering it to obtain an environmental barrier coating bonding layer material.
[0012] Preferably, in step S1), the solution is a mixed solution of concentrated nitric acid and anhydrous ethanol in a volume ratio of 1:(3-4), and the mixing is carried out under stirring conditions, the stirring rate is 350-450 r / min, and the time is 0.5-2 h.
[0013] Preferably, step S2) is specifically as follows:
[0014] The mixed solution is added into concentrated aqueous ammonia, stirred, and ultrasonically dispersed to obtain a precipitate;
[0015] The precipitate is filtered, washed, and then calcined to remove moisture. The resulting mixture is sintered to obtain HfO 2 and Y 2 O 3 Mixed powder;
[0016] The stirring rate is 250-350 r / min, and the time is 0.5-1 h; the ultrasonic dispersion time is 0.5-1 h; the calcination temperature is 900-1100° C., and the time is 2-5 h; the sintering temperature is 1300-1500° C., and the time is 8-15 h.
[0017] Preferably, in step S3), the solvent of the ball milling is anhydrous ethanol, the mass ratio of the mixed powder and Si mixed powder, grinding balls and anhydrous ethanol is 1: (1-2): 1.5, the rotation speed of the ball mill is 300-500 r / min, and the time is 4-10 h.
[0018] Preferably, in step S3), the binder is selected from PVA, and the mass ratio of the slurry after ball milling to the binder is (100-200):1.
[0019] Preferably, in step S4), the air inlet temperature of the spray drying is 160-200°C, the air outlet temperature is 130-150°C, the centrifugal frequency is 150-200 Hz, and the peristaltic pump feed rate is 30-50 r / min; the sintering temperature is 1200-1500°C, and the time is 12-24 h.
[0020] The present application also provides an environmental barrier composite material, comprising a substrate and an environmental barrier coating composited on the surface of the substrate, wherein the bonding layer material of the environmental barrier coating is the bonding layer material or the bonding layer material prepared by the preparation method.
[0021] Preferably, the environmental barrier coating is prepared by plasma spraying, the current of the plasma spraying is 500A, the argon flow rate is 30~50sccm, the hydrogen flow rate is 8~20sccm, the powder feeding rate is 15~30g / min, and the spraying distance is 100~150mm; the thickness of the environmental barrier coating is 0.05~0.1mm.
[0022] The present application provides an environmental barrier coating bonding layer material, which includes Si, HfO 2 and Y 2 O 3 ; wherein the HfO 2 and the Y 2 O 3 The molar ratio of HfO is x:(1-x). 2 The molar ratio of Si to HfO is (0.2:0.8) to (0.8:0.2); wherein 0.8≤x≤0.9; in the environmental barrier coating bonding layer material provided in the present application, Si and HfO 2 When the molar ratio of Si and HfO is greater than 1, 2 and Y 2 O 3The interface between the coating and the substrate is a dense and continuous Si layer with high bonding strength. 2 Evenly distributed in the coating, the SiO 2 The reaction generates HfSiO 4 , preventing the micro cracks from expanding and overlapping, thereby improving the overall toughness of the coating, so that the obtained coating has a longer service life at 1350℃; Si and HfO 2 When the molar ratio of Si and HfO is less than 1, 2 and Y 2 O 3 The formed coating is HfSiO which is stable at high temperature, has low oxygen diffusion rate and high melting point. 4 is the main phase, and Y doping can increase the c-HfO 2 The Y phase content reduces the thermal conductivity of the coating, which is beneficial to improve the temperature bearing capacity of the coating, so that the coating still has a protective effect on the CMC substrate at 1500℃; and 2 O 3 Can stabilize HfO 2 , making HfO 2 At high temperatures, more of them are stable in the cubic phase, which reduces the thermal conductivity of the coating and makes the coating have better high-temperature stability. Therefore, the environmental barrier coating bonding layer material provided by the present application introduces Si, HfO 2 and Y 2 O 3 , and adjust the content relationship so that the obtained coating has a long life at 1350℃ and has good temperature bearing capacity at 1500℃, and can be applied to different service environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Si-HfO prepared in Examples 1 to 4 of the present invention 2 +Y 2 O 3 Microscopic morphology photos of powder materials;
[0024] Figure 2 The Si-HfO provided by the present invention 2 +Y 2 O 3 Schematic diagram of the coating structure. DETAILED DESCRIPTION
[0025] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0026] In view of the existing technology of Si+HfO 2The system cannot be used at higher temperatures. The present application provides an environmental barrier coating bonding layer material, which is made of Si, HfO 2 and Y 2 O 3 As a coating system, and adjusting the ratio of the three, the obtained coating can meet the use requirements at different temperatures and has the characteristics of temperature sensing and self-adaptation. Specifically, the embodiment of the present invention discloses an environmental barrier coating bonding layer material, including Si, HfO 2 and Y 2 O 3 , the HfO 2 and the Y 2 O 3 The molar ratio of HfO is x:(1-x). 2 The molar ratio of x to Si is (0.2:0.8) to (0.8:0.2); wherein 0.8≤x≤0.9.
[0027] In the environmental barrier coating bonding layer material provided in the present application, the HfO 2 and the Y 2 O 3 The molar ratio is x: (1-x), wherein 0.8≤x≤0.9; for example, the HfO 2 and the Y 2 O 3 The molar ratio of Y is 0.9:0.1 or 0.8:0.2. 2 O 3 Can stabilize HfO 2 , which can make hafnium oxide more stable in the cubic phase at high temperature, so that the coating has better high-temperature stability. If the yttrium oxide content is not in the above range, hafnium oxide will have more monoclinic phase at high temperature, which makes the coating have poor high-temperature stability.
[0028] In the environmental barrier coating bonding layer material provided in the present application, the HfO 2 The molar ratio of HfO to Si is (0.2:0.8) to (0.8:0.2). Specifically, the HfO 2 The molar ratio of Si to HfO is 0.3:0.7, 0.4:0.6, 0.5:0.5, 0.6:0.4, 0.7:0.3 or 0.8:0.2; when the Si content is high (Si to HfO 2 When the molar ratio is greater than 1), the obtained Si+HfO 2 +Y 2 O 3 (Si-HfO 2 +Y 2 O 3 )The interface between the coating and the CMC substrate is a dense and continuous Si layer with high bonding strength; HfO2 Uniformly distributed in Si-HfO 2 +Y 2 O 3 In the coating, SiO formed by oxidation 2 The reaction generates HfSiO 4 , preventing the micro cracks from expanding and overlapping, thereby improving the overall toughness of the coating, and the coating has a long service life at 1350℃; and when HfO 2 When the content is high (Si and HfO 2 When the molar ratio of Si-HfO is less than 1), the obtained Si-HfO 2 +Y 2 O 3 The coating is HfSiO which is stable at high temperature, has low oxygen diffusion rate and high melting point. 4 is the main phase, and Y doping can increase the c-HfO 2 The phase content can reduce the thermal conductivity of the coating, which is beneficial to improve the temperature bearing capacity of the coating, so that the coating still has a protective effect on the CMC substrate at 1500°C. 2 The ratio of Y 2 O 3 The coating formed by the bonding layer material can be made suitable for different high temperature environments.
[0029] Furthermore, the present application also provides a method for preparing an environmental barrier coating bonding layer material, comprising the following steps:
[0030] S1) HfOCl 2 8H 2 O and Y 2 O 3 Mixing in a solution in a molar ratio of x:(1-x) to obtain a mixed solution, wherein 0.8≤x≤0.9;
[0031] S2) The mixed solution is sequentially precipitated, filtered, washed, calcined, and sintered to obtain HfO 2 and Y 2 O 3 Mixed powder;
[0032] S3) mixing the mixed powder and Si, ball milling, and then mixing with a binder to obtain a mixed slurry; HfO in the mixed powder 2 The molar ratio of Si is (0.2:0.8)~(0.8:0.2);
[0033] S4) spray-drying the mixed slurry and then sintering it to obtain an environmental barrier coating bonding layer material.
[0034] In the preparation method of the environmental barrier coating bonding layer material provided in the present application, the present application firstly2 8H 2 O and Y 2 O 3 The mixed solution is obtained according to the molar ratio of x: (1-x), wherein 0.8≤x≤0.9; in this process, the solution is specifically a mixed solution of concentrated nitric acid and anhydrous ethanol in a volume ratio of 1: (3-4), and the mixed solution is used to convert HfOCl 2 8H 2 O and Y 2 O 3 Fully dissolved; stirring is performed during the mixing process, the stirring rate is 350~450r / min, and the time is 0.5~2h, specifically, the stirring rate is 380~420r / min, and the time is 1~1.5h.
[0035] The present invention then sequentially precipitates, filters, washes, calcines and sinters the mixed solution to obtain HfO 2 and Y 2 O 3 In this process, HfO was obtained by chemical coprecipitation. 2 and Y 2 O 3 The specific process is as follows:
[0036] The mixed solution is added dropwise into concentrated ammonia water, stirred, and ultrasonically dispersed to obtain a precipitate;
[0037] The precipitate is filtered, washed, and calcined to remove moisture to obtain an initial product;
[0038] The initial product is ground and then sintered at high temperature to obtain HfO 2 and Y 2 O 3 of mixed powder.
[0039] In the above process, the addition of concentrated ammonia is beneficial to the formation of HfO 2 and Y 2 O 3The precipitation is carried out at a stirring rate of 250-350 r / min and a time of 0.5-1 h. Specifically, the stirring rate is 280-320 r / min. The ultrasonic dispersion time is 0.5-1 h. The calcination temperature is 900-1100°C and the time is 2-5 h. Specifically, the calcination temperature is 950-1000°C and the time is 3-4 h. The calcination is to remove moisture from the washed product. If the temperature is too high, the powder is prone to agglomeration. If the temperature is too low, the moisture cannot be completely removed. The sintering temperature is 1300-1500°C and the time is 8-15 h. Specifically, the sintering temperature is 1350-1400°C and the time is 9-12 h. The sintering is to promote grain growth.
[0040] The present application then mixes the above mixed powder and Si, ball mills, and mixes the obtained slurry with a binder to obtain a mixed slurry; in the above process, the ball milling can achieve HfO 2 , Y 2 O 3 and Si are uniformly mixed; the solvent of the ball mill is anhydrous ethanol, the mass ratio of the mixed powder and Si mixed powder, grinding balls and anhydrous ethanol is 1: (1-2): 1.5, the speed of the ball mill is 300-500r / min, and the time is 4-10h; specifically, the mass ratio of the mixed powder and Si mixed powder, grinding balls and anhydrous ethanol is 1: (1.3-1.7): 1.5, the speed of the ball mill is 400-480r / min, and the time is 5-8h. The binder is PVA, and the mass ratio of the slurry after ball milling to the binder is (100-200): 1; specifically, the mass ratio of the slurry after ball milling to the binder is (120-180): 1.
[0041] According to the present invention, the initial mixed powder is finally spray dried and sintered to obtain the environmental barrier coating bonding layer material; in this process, the air inlet temperature of the spray drying is 160~200°C, the air outlet temperature is 130~150°C, the centrifugal frequency is 150~200Hz, and the peristaltic pump feed rate is 30~50r / min; specifically, the air inlet temperature of the spray drying is 180~200°C, the air outlet temperature is 130~140°C, the centrifugal frequency is 160~180Hz, and the peristaltic pump feed rate is 35~45r / min; the sintering temperature is 1200~1500°C, and the time is 12~24h, specifically, the sintering temperature is 1250~1350°C, and the time is 18~20h. The spray drying is used to form a mixed powder with a specific fluidity and loose density; when the air inlet, air outlet, and centrifugal frequency are too high, the droplets dry quickly to form too fine powder, with high loose density and poor fluidity; when the air inlet, air outlet, and centrifugal frequency are too low, the solvent in the droplets evaporates slowly, forming powder that is easy to stick to the wall, with low loose density and poor fluidity; the fluidity of the adhesive layer material of the present application is (22~48) s / 50g, and the loose density is 1.0~2.0g / cm 3 .
[0042] The present application also provides an environmental barrier composite material, which includes a substrate and an environmental barrier coating composited on the surface of the substrate, wherein the bonding layer material of the environmental barrier coating is the bonding layer material described in the above scheme, such as Figure 2 shown.
[0043] In the present application, the substrate is preferably a CMC substrate, and the environmental barrier coating is prepared by plasma spraying, especially by an atmospheric plasma spraying method, the current of the plasma spraying is 500A, the argon flow rate is 30~50sccm, the hydrogen flow rate is 8~20sccm, the powder feeding rate is 15~30g / min, and the spraying distance is 100~150mm; the thickness of the environmental barrier coating is 0.05~0.1mm; specifically, the argon flow rate of the plasma spraying is 30~45sccm, the hydrogen flow rate is 8~16sccm, the powder feeding rate is 20~28g / min, and the spraying distance is 120~140mm; the thickness of the environmental barrier coating is 0.06~0.08mm.
[0044] The present invention prepares Si-HfO by chemical coprecipitation and spray granulation. 2 +Y 2 O 3 Environmental barrier coating bonding layer powder, by adjusting the mixing ratio of raw materials, can obtain bonding layer materials suitable for different service environments; bonding layer material Si-HfO 2 +Y 2 O 3The preparation process is simple, the cost of the chemical reagents used is low, and the composition of the coating bonding layer material can be precisely controlled according to the actual service environment. It is expected to be applied on the surface of the hot end components of the new generation of high thrust-to-weight ratio aircraft engines ceramic-based composite materials.
[0045] In order to further understand the present invention, the environmental barrier coating bonding layer material, the preparation method thereof and the environmental barrier composite material provided by the present invention are described in detail below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0046] The Si-HfO involved in the present invention 2 +Y 2 O 3 The test methods for powder materials and coating properties include:
[0047] Test the powder bulk density according to GB / T 1479.1;
[0048] Test powder fluidity according to GB / T 1482;
[0049] Test the bonding strength of the coating according to HB 5476;
[0050] The coating samples were placed in a high-temperature furnace to test the coating's anti-oxidation properties at 1350°C;
[0051] The anti-oxidation cycle performance of the coating at 1500°C was tested according to AETF58A “Test method for thermal cycle resistance of coatings”.
[0052] Example 1
[0053] HfOCl 2 8H 2 O and Y 2 O 3 According to the molar ratio of 0.9:0.1, add concentrated nitric acid and anhydrous ethanol in a volume ratio of 1:3, stir well, the stirring rate is 400r / min, the stirring time is 1h, and obtain a mixed solution;
[0054] The mixed solution was added dropwise into an excess of concentrated ammonia water, stirred, and ultrasonically dispersed to form a precipitate. The stirring rate was 300 r / min, the stirring time was 1 h, and the ultrasonic time was 1 h.
[0055] The above precipitate was filtered, washed, and calcined to remove moisture. The washing agent was deionized water. The calcination temperature was 1000°C and the calcination time was 4 hours.
[0056] The above product is slightly ground and sintered at high temperature to obtain HfO 2 +Y 2 O 3 Mixed powder, the sintering temperature is 1300°C, and the sintering time is 12h;
[0057] HfO 2 +Y 2 O 3 and Si are mechanically mixed and then ball milled to obtain a ball milled mixed slurry, wherein HfO 2 The molar ratio of Si to Si is 0.4:0.6, the ball milling balls are agate balls, the ball milling solvent is anhydrous ethanol, the mass ratio of the mixed powder, the grinding balls and anhydrous ethanol is 1:2:1.5, the ball milling speed is 400r / min, and the ball milling time is 8h;
[0058] The mixed slurry is mixed with PVA binder and spray-dried, and the obtained product is sintered at high temperature, ground, and sieved to obtain Si-HfO 2 +Y 2 O 3 Temperature-sensitive adaptive environmental barrier coating bonding layer powder; wherein the mass ratio of PVA binder to mixed slurry is 1:200, the inlet temperature of spray drying is 180°C, the outlet temperature is 130°C, the centrifugal frequency is 150Hz, and the peristaltic pump feed rate is 40r / min; the high-temperature sintering temperature is 1250°C, and the sintering time is 24h; the obtained powder has a fluidity of 42s / 50g and a bulk density of 1.2g / cm 3 .
[0059] The bonding layer powder obtained above was plasma sprayed on the CMC substrate to prepare Si-HfO 2 +Y 2 O 3 Coating; the plasma spraying adopts atmospheric plasma spraying equipment, and the spraying process adopted is: spraying current 500A, argon flow rate 40sccm, hydrogen flow rate 12sccm, powder feeding rate 20g / min, spraying distance 120mm, and coating thickness is 0.08mm.
[0060] The performance of the coating was tested according to the above method. The specific results were as follows: the bonding strength of the coating was 22.3 MPa, and after oxidation at 1350°C for 500 hours, the coating was continuous, dense, and had no peeling. The thickness of the formed thermally grown oxide (TGO) oxide layer was 10.6 μm.
[0061] Example 2
[0062] HfOCl 2 8H 2 O and Y 2 O 3 According to the molar ratio of 0.9:0.1, concentrated nitric acid and anhydrous ethanol were added to a solution with a volume ratio of 1:3, and stirred thoroughly at a stirring rate of 400 r / min for 1 h to obtain a mixed solution;
[0063] The mixed solution was added dropwise into an excess of concentrated ammonia water, stirred, and ultrasonically dispersed to form a precipitate. The stirring rate was 300 r / min, the stirring time was 1 h, and the ultrasonic time was 1 h.
[0064] The above precipitate was filtered, washed, and calcined to remove moisture. The washing agent was deionized water. The calcination temperature was 900°C and the calcination time was 4 hours.
[0065] The above product is slightly ground and sintered at high temperature to obtain HfO 2 +Y 2 O 3 Mixed powder, the sintering temperature is 1500°C, and the sintering time is 12h;
[0066] HfO 2 +Y 2 O 3 and Si are mechanically mixed and then ball milled to obtain a ball milled mixed slurry, wherein HfO 2 The molar ratio of Si to Si is 0.4:0.6, the ball milling balls are agate balls, the ball milling solvent is anhydrous ethanol, the mass ratio of the mixed powder, the grinding balls and anhydrous ethanol is 1:2:1.5, the ball milling speed is 400r / min, and the ball milling time is 8h;
[0067] The mixed slurry is mixed with PVA binder and spray-dried, and the obtained product is sintered at high temperature, ground, and sieved to obtain Si-HfO 2 +Y 2 O 3 Temperature-sensitive adaptive environmental barrier coating bonding layer material; wherein the mass ratio of PVA binder to mixed slurry is 1:200, the inlet temperature of spray drying is 180°C, the outlet temperature is 130°C, the centrifugal frequency is 150Hz, and the peristaltic pump feed rate is 40r / min; the high-temperature sintering temperature is 1350°C, and the sintering time is 24h; the obtained powder flowability is 48s / 50g, and the bulk density is 1.5g / cm 3 .
[0068] The bonding layer powder obtained above was plasma sprayed on the CMC substrate to prepare Si-HfO 2 +Y 2 O 3 Coating; the plasma spraying adopts atmospheric plasma spraying equipment, and the spraying process adopted is: spraying current 500A, argon flow rate 40sccm, hydrogen flow rate 12sccm, powder feeding rate 20g / min, spraying distance 120mm, and coating thickness is 0.08mm.
[0069] The performance of the coating was tested according to the above method. The specific results were as follows: the bonding strength of the coating was 22.8 MPa, and after oxidation at 1350°C for 500 hours, the coating was continuous, dense, and had no peeling. The thickness of the formed thermally grown oxide (TGO) oxide layer was 10.6 μm.
[0070] Example 3
[0071] HfOCl 2 8H 2 O and Y 2 O 3 According to the molar ratio of 0.9:0.1, concentrated nitric acid and anhydrous ethanol were added to a solution with a volume ratio of 1:3, and stirred thoroughly at a stirring rate of 400 r / min for 1 h to obtain a mixed solution;
[0072] The mixed solution was added dropwise into an excess of concentrated ammonia water, stirred, and ultrasonically dispersed to form a precipitate. The stirring rate was 300 r / min, the stirring time was 1 h, and the ultrasonic time was 1 h.
[0073] The above precipitate was filtered, washed, and calcined to remove moisture. The washing agent was deionized water. The calcination temperature was 1000°C and the calcination time was 4 hours.
[0074] The above product is slightly ground and sintered at high temperature to obtain HfO 2 +Y 2 O 3 Mixed powder, the sintering temperature is 1300°C, and the sintering time is 12h;
[0075] HfO 2 +Y 2 O 3 and Si are mechanically mixed and then ball milled to obtain a ball milled mixed slurry, wherein HfO 2 The molar ratio of Si to Si is 0.6:0.4, the ball milling balls are agate balls, the ball milling solvent is anhydrous ethanol, the mass ratio of the mixed powder, the grinding balls and anhydrous ethanol is 1:2:1.5, the ball milling speed is 400r / min, and the ball milling time is 8h;
[0076] The mixed slurry is mixed with PVA binder and spray-dried, and the obtained product is sintered at high temperature, ground, and sieved to obtain Si-HfO 2 +Y 2 O 3Temperature-sensitive adaptive environmental barrier coating bonding layer powder; wherein the mass ratio of PVA binder to mixed slurry is 1:200, the inlet temperature of spray drying is 180°C, the outlet temperature is 130°C, the centrifugal frequency is 150Hz, and the peristaltic pump feed rate is 40r / min; the high-temperature sintering temperature is 1250°C, and the sintering time is 24h; the obtained powder has a flowability of 22s / 50g and a bulk density of 1.8g / cm 3 .
[0077] The bonding layer powder obtained above was plasma sprayed on the CMC substrate to prepare Si-HfO 2 +Y 2 O 3 Coating; the plasma spraying adopts atmospheric plasma spraying equipment, and the spraying process adopted is: spraying current 500A, argon flow rate 40sccm, hydrogen flow rate 12sccm, powder feeding rate 20g / min, spraying distance 120mm, and coating thickness is 0.07mm.
[0078] The performance of the coating was tested according to the above method, and the specific results were: the coating bonding strength was 19.3MPa, the coating was continuous, dense, and had no peeling after cyclic oxidation at 1500℃ for 100h, and the thickness of the formed thermally grown oxide (TGO) oxide layer was 7.9μm.
[0079] Example 4
[0080] HfOCl 2 8H 2 O and Y 2 O 3 According to the molar ratio of 0.9:0.1, concentrated nitric acid and anhydrous ethanol were added to a solution with a volume ratio of 1:3, and stirred thoroughly at a stirring rate of 400 r / min for 1 h to obtain a mixed solution;
[0081] The mixed solution was added dropwise into an excess of concentrated ammonia water, stirred, and ultrasonically dispersed to form a precipitate. The stirring rate was 300 r / min, the stirring time was 1 h, and the ultrasonic time was 1 h.
[0082] The above precipitate was filtered, washed, and calcined to remove moisture. The washing agent was deionized water. The calcination temperature was 900°C and the calcination time was 4 hours.
[0083] The above product is slightly ground and sintered at high temperature to obtain HfO 2 +Y 2 O 3 Mixed powder, the sintering temperature is 1500°C, and the sintering time is 12h;
[0084] HfO 2 +Y 2 O3 and Si are mechanically mixed and then ball milled to obtain a ball milled mixed slurry, wherein HfO 2 The molar ratio of Si to Si is 0.6:0.4, the ball milling balls are agate balls, the ball milling solvent is anhydrous ethanol, the mass ratio of the mixed powder, the grinding balls and anhydrous ethanol is 1:2:1.5, the ball milling speed is 400r / min, and the ball milling time is 8h;
[0085] The mixed slurry is mixed with PVA binder and spray-dried, and the obtained product is sintered at high temperature, ground, and sieved to obtain Si-HfO 2 +Y 2 O 3 Temperature-sensitive adaptive environmental barrier coating bonding layer powder; wherein the mass ratio of PVA binder to mixed slurry is 1:200, the inlet temperature of spray drying is 180°C, the outlet temperature is 130°C, the centrifugal frequency is 150Hz, and the peristaltic pump feed rate is 40r / min; the high-temperature sintering temperature is 1350°C, and the sintering time is 24h; the obtained powder has a flowability of 27s / 50g and a bulk density of 2.0g / cm 3 .
[0086] The bonding layer powder obtained above was plasma sprayed on the CMC substrate to prepare Si-HfO 2 +Y 2 O 3 Coating; Among them, the plasma spraying adopts atmospheric plasma spraying equipment, and the spraying process adopted is: spraying current 500A, argon flow rate 40sccm, hydrogen flow rate 12sccm, powder feeding rate 20g / min, spraying distance 120mm, and coating thickness is 0.07mm.
[0087] The performance of the coating was tested according to the above method, and the specific results were: the coating bonding strength was 20.4MPa, the coating was continuous, dense, and had no peeling after cyclic oxidation at 1500℃ for 100h, and the thickness of the formed thermally grown oxide (TGO) oxide layer was 7.2μm.
[0088] Figure 1 The four photos are respectively Si-HfO prepared in Example 1, Example 2, Example 3 and Example 4. 2 +Y 2 O 3 SEM images of powders, Figure 1 It can be seen that the bonding layer powder prepared in this embodiment is uniform, dense, and has a high sphericity.
[0089] Comparative Example 1
[0090] The Si coating was prepared on the CMC substrate by plasma spraying; the plasma spraying used an atmospheric plasma spraying equipment with a spraying current of 500A, an argon flow rate of 40sccm, a hydrogen flow rate of 12sccm, a powder feeding rate of 20g / min, a spraying distance of 120mm, and a coating thickness of 0.10mm.
[0091] The performance of the coating was tested according to the above method, and the specific results were: the coating bonding strength was 24.7 MPa, and after oxidation at 1350°C for 500 hours, the thickness of the thermally grown oxide (TGO) oxide layer was 16.8 μm.
[0092] Comparative Example 2
[0093] The Si coating was prepared on the CMC substrate by plasma spraying; the plasma spraying used an atmospheric plasma spraying equipment with a spraying current of 500A, an argon flow rate of 40sccm, a hydrogen flow rate of 12sccm, a powder feeding rate of 20g / min, a spraying distance of 120mm, and a coating thickness of 0.10mm.
[0094] The performance of the coating was tested according to the above method, and the specific results were as follows: the coating bonding strength was 24.7 MPa, the coating bulged after cyclic oxidation at 1500°C for 8 hours, and the coating peeled off after oxidation for 10 hours. The thickness of the thermally grown oxide (TGO) oxide layer formed was 32.4 μm.
[0095] Comparative Example 3
[0096] HfOCl 2 8H 2 O and Y 2 O 3 According to the molar ratio of 0.95:0.05, it was added into a solution of concentrated nitric acid and anhydrous ethanol in a volume ratio of 1:3, and stirred thoroughly at a stirring rate of 400 r / min for 1 h to obtain a mixed solution;
[0097] The mixed solution was added dropwise into an excess of concentrated ammonia water, stirred, and ultrasonically dispersed to form a precipitate. The stirring rate was 300 r / min, the stirring time was 1 h, and the ultrasonic time was 1 h.
[0098] The above precipitate was filtered, washed, and calcined to remove moisture. The washing agent was deionized water. The calcination temperature was 900°C and the calcination time was 4 hours.
[0099] The above product is slightly ground and sintered at high temperature to obtain HfO 2 +Y 2 O 3 Mixed powder, the sintering temperature is 1500°C, and the sintering time is 12h;
[0100] HfO 2 +Y2 O 3 and Si are mechanically mixed and then ball milled to obtain a ball milled mixed slurry, wherein HfO 2 The molar ratio of Si to Si is 0.6:0.4, the ball milling balls are agate balls, the ball milling solvent is anhydrous ethanol, the mass ratio of the mixed powder, the grinding balls and anhydrous ethanol is 1:2:1.5, the ball milling speed is 400r / min, and the ball milling time is 8h;
[0101] The mixed slurry is mixed with PVA binder and spray-dried, and the obtained product is sintered at high temperature, ground, and sieved to obtain Si-HfO 2 +Y 2 O 3 Temperature-sensitive adaptive environmental barrier coating bonding layer powder; wherein the mass ratio of PVA binder to mixed slurry is 1:200, the inlet temperature of spray drying is 180°C, the outlet temperature is 130°C, the centrifugal frequency is 150Hz, and the peristaltic pump feed rate is 40r / min; the high-temperature sintering temperature is 1350°C, and the sintering time is 24h; the obtained powder has a fluidity of 31s / 50g and a bulk density of 1.9g / cm 3 .
[0102] The bonding layer powder obtained above was plasma sprayed on the CMC substrate to prepare Si-HfO 2 +Y 2 O 3 Coating; the plasma spraying adopts atmospheric plasma spraying equipment, and the spraying process adopted is: spraying current 500A, argon flow rate 40sccm, hydrogen flow rate 12sccm, powder feeding rate 20g / min, spraying distance 120mm, and coating thickness is 0.07mm.
[0103] The performance of the coating was tested according to the above method. The specific results were as follows: the coating bonding strength was 19.8 MPa, the coating cracked after cyclic oxidation at 1500°C for 60 hours, and the thickness of the formed TGO oxide layer was 16.6 μm.
[0104] Comparative Example 4
[0105] HfOCl 2 8H 2 O was added into a solution of concentrated nitric acid and anhydrous ethanol in a volume ratio of 1:3, and stirred thoroughly at a stirring rate of 400 r / min for 1 h to obtain a mixed solution;
[0106] The mixed solution was added dropwise into an excess of concentrated ammonia water, stirred, and ultrasonically dispersed to form a precipitate. The stirring rate was 300 r / min, the stirring time was 1 h, and the ultrasonic time was 1 h.
[0107] The above precipitate was filtered, washed, and calcined to remove moisture. The washing agent was deionized water. The calcination temperature was 900°C and the calcination time was 4 hours.
[0108] The above product is slightly ground and sintered at high temperature to obtain HfO 2 Powder material, the sintering temperature is 1500°C, and the sintering time is 12h;
[0109] HfO 2 After mechanical mixing with Si, ball milling is performed to obtain a ball milling mixed slurry, wherein HfO 2 The molar ratio of Si to Si is 0.6:0.4, the ball milling balls are agate balls, the ball milling solvent is anhydrous ethanol, the mass ratio of the mixed powder, the grinding balls and anhydrous ethanol is 1:2:1.5, the ball milling speed is 400r / min, and the ball milling time is 8h;
[0110] The mixed slurry is mixed with PVA binder and spray-dried, and the obtained product is sintered at high temperature, ground, and sieved to obtain Si-HfO 2 Powder; wherein the mass ratio of PVA binder to mixed slurry is 1:200, the air inlet temperature of spray drying is 180°C, the air outlet temperature is 130°C, the centrifugal frequency is 150Hz, and the peristaltic pump feed rate is 40r / min; the high-temperature sintering temperature is 1350°C, and the sintering time is 24h; the obtained powder has a fluidity of 33s / 50g and a bulk density of 1.9g / cm 3 .
[0111] The Si-HfO 2 Preparation of Si-HfO powder on CMC substrate by plasma spraying 2 Coating; the plasma spraying adopts atmospheric plasma spraying equipment, and the spraying process adopted is: spraying current 500A, argon flow rate 40sccm, hydrogen flow rate 12sccm, powder feeding rate 20g / min, spraying distance 120mm, and coating thickness is 0.07mm.
[0112] The performance of the coating was tested according to the above method. The specific results were as follows: the coating bonding strength was 19.5 MPa, the coating peeled off after cyclic oxidation at 1500°C for 20 hours, and the thickness of the formed TGO oxide layer was 19.3 μm.
[0113] Comparative Example 5
[0114] HfOCl 2 8H 2 O and Y 2 O 3According to the molar ratio of 0.7:0.3, it was added into a solution of concentrated nitric acid and anhydrous ethanol in a volume ratio of 1:3, and stirred thoroughly at a stirring rate of 400 r / min for 1 h to obtain a mixed solution;
[0115] The mixed solution was added dropwise into an excess of concentrated ammonia water, stirred, and ultrasonically dispersed to form a precipitate. The stirring rate was 300 r / min, the stirring time was 1 h, and the ultrasonic time was 1 h.
[0116] The above precipitate was filtered, washed, and calcined to remove moisture. The washing agent was deionized water. The calcination temperature was 900°C and the calcination time was 4 hours.
[0117] The above product is slightly ground and sintered at high temperature to obtain HfO 2 +Y 2 O 3 Mixed powder, the sintering temperature is 1500°C, and the sintering time is 12h;
[0118] HfO 2 +Y 2 O 3 and Si are mechanically mixed and then ball milled to obtain a ball milled mixed slurry, wherein HfO 2 The molar ratio of Si to Si is 0.6:0.4, the ball milling balls are agate balls, the ball milling solvent is anhydrous ethanol, the mass ratio of the mixed powder, the grinding balls and anhydrous ethanol is 1:2:1.5, the ball milling speed is 400r / min, and the ball milling time is 8h;
[0119] The mixed slurry is mixed with PVA binder and spray-dried, and the obtained product is sintered at high temperature, ground, and sieved to obtain Si-HfO 2 +Y 2 O 3 Temperature-sensitive adaptive environmental barrier coating bonding layer powder; wherein the mass ratio of PVA binder to mixed slurry is 1:200, the inlet temperature of spray drying is 180°C, the outlet temperature is 130°C, the centrifugal frequency is 150Hz, and the peristaltic pump feed rate is 40r / min; the high-temperature sintering temperature is 1350°C, and the sintering time is 24h; the obtained powder has a flowability of 35s / 50g and a bulk density of 2.1g / cm 3 .
[0120] The bonding layer powder obtained above was plasma sprayed on the CMC substrate to prepare Si-HfO 2 +Y 2 O 3Coating; the plasma spraying adopts atmospheric plasma spraying equipment, and the spraying process adopted is: spraying current 500A, argon flow rate 40sccm, hydrogen flow rate 12sccm, powder feeding rate 20g / min, spraying distance 120mm, and coating thickness is 0.07mm.
[0121] The performance of the coating was tested according to the above method, and the specific results were: the coating bonding strength was 19.8MPa, the coating cracked after cyclic oxidation at 1500℃ for 45h, and the thickness of the formed TGO oxide layer was 19.3μm.
[0122] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0123] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An environmental barrier coating bonding layer material, comprising Si, HfO2 and Y2O3, wherein the molar ratio of HfO2 to Y2O3 is x:(1-x), and the molar ratio of HfO2 to Si is (0.2:0.8) to (0.8:0.2); wherein, 0.8≤x≤0.9。 2. The environmental barrier coating bonding layer material according to claim 1, characterized in that: The molar ratio of the HfO2 to the Si is (0.4:0.6) to (0.6:0.4).
3. The method for preparing the environmental barrier coating bonding layer material according to claim 1, comprising the following steps: S1) mixing HfOCl2·8H2O and Y2O3 in a solution at a molar ratio of x:(1-x) to obtain a mixed solution, wherein 0.8≤x≤0.9; S2) subjecting the mixed solution to precipitation, filtration, washing, calcination and sintering in sequence to obtain a mixed powder of HfO2 and Y2O3; S3) mixing the mixed powder and Si, ball milling, and then mixing with a binder to obtain a mixed slurry; the molar ratio of HfO2 to Si in the mixed powder is (0.2:0.8) to (0.8:0.2); S4) spray-drying the mixed slurry and then sintering it to obtain an environmental barrier coating bonding layer material.
4. The preparation method according to claim 3, characterized in that: In step S1), the solution is a mixed solution of concentrated nitric acid and anhydrous ethanol in a volume ratio of 1:(3-4), and the mixing is carried out under stirring conditions, the stirring rate is 350-450 r / min, and the time is 0.5-2 h.
5. The preparation method according to claim 3, characterized in that: Step S2) is specifically as follows: The mixed solution is added into concentrated aqueous ammonia, stirred, and ultrasonically dispersed to obtain a precipitate; The precipitate is filtered and washed, and then calcined to remove moisture, and the obtained mixture is sintered to obtain a mixed powder of HfO2 and Y2O3; The stirring rate is 250-350 r / min, and the time is 0.5-1 h; the ultrasonic dispersion time is 0.5-1 h; the calcination temperature is 900-1100° C., and the time is 2-5 h; the sintering temperature is 1300-1500° C., and the time is 8-15 h.
6. The preparation method according to claim 3, characterized in that: In step S3), the solvent of the ball milling is anhydrous ethanol, the mass ratio of the mixed powder and Si mixed powder, grinding balls and anhydrous ethanol is 1: (1-2): 1.5, the rotation speed of the ball mill is 300-500 r / min, and the time is 4-10 h.
7. The preparation method according to claim 3, characterized in that: In step S3), the binder is selected from PVA, and the mass ratio of the slurry after ball milling to the binder is (100-200):
1.
8. The preparation method according to claim 3, characterized in that: In step S4), the air inlet temperature of the spray drying is 160-200°C, the air outlet temperature is 130-150°C, the centrifugal frequency is 150-200 Hz, and the peristaltic pump feed rate is 30-50 r / min; the sintering temperature is 1200-1500°C, and the time is 12-24 hours.
9. An environmental barrier composite material, comprising a substrate and an environmental barrier coating composited on the surface of the substrate, wherein the bonding layer material of the environmental barrier coating is the bonding layer material according to any one of claims 1 to 2 or the bonding layer material prepared by the preparation method according to any one of claims 3 to 8.
10. The environmental barrier composite material according to claim 9, characterized in that: The environmental barrier coating is prepared by plasma spraying, the current of the plasma spraying is 500A, the argon flow rate is 30~50sccm, the hydrogen flow rate is 8~20sccm, the powder feeding rate is 15~30g / min, and the spraying distance is 100~150mm; the thickness of the environmental barrier coating is 0.05~0.1mm.